A case of longitudinally extensive transverse myelitis with an isolated pontine lesion following epidural and spinal anesthesia for cesarean section - Yuki Kitazaki; Asako Ueno; Kenichiro Maeda; Rei Asano; Hiroyuki Satomi; Taro Nishio; Yasunari Nakamoto; Tadanori Hamano (eNeurologicalSci, 2020)
Severe neurologic complications following epidural and spinal anesthesia rarely occur. Transverse myelitis has been reported as a rare complication of epidural or spinal anesthesia. We report a case of longitudinally extensive transverse myelitis and an isolated pontine lesion, which responded to immunotherapy. The patient was a 31-year-old pregnant woman who underwent elective cesarean section under epidural and spinal anesthesia. Though the insertions of the epidural and spinal catheters were smooth, she experienced back pain and transient hearing loss during epidural anesthesia. Postoperatively, she exhibited severe motor weakness in both lower extremities, neuralgia below the level of Th10 dermatome, and urinary retention. Magnetic resonance imaging showed longitudinally extensive transverse myelitis from T6 to T10 with a ring-shaped enhanced lesion and an isolated pontine lesion. These findings on magnetic resonance imaging were suggestive of autoimmune diseases such as neuromyelitis optica. The patient was diagnosed with an immunoreactive disease triggered by epidural or spinal anesthesia and was administered high-dose methylprednisolone, which led to the improvement in clinical symptoms. Clinicians should be aware of the possibility of the development of longitudinally extensive transverse myelitis and isolated pontine lesions after cesarean section under epidural and spinal anesthesia.